Internet gaming disorder: Its prevalence and associated gaming behavior, anxiety, and depression among high school male students, Dammam, Saudi Arabia - Mohammed A Alhamoud; Ahmed A Alkhalifah; Abdullatif K Althunyan; Tajammal Mustafa; Hatem A Alqahtani; Feras A Al Awad (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Video games have become popular in the last few decades, resulting in an increase in reported negative consequences. This study aimed to assess the prevalence of internet gaming disorder (IGD), its association with gaming behavior, depression, and anxiety in male high school students. MATERIALS AND METHODS: This cross-sectional study involved male high school students in Dammam. Schools were selected using stratified random sampling, and data were collected using a self-administered questionnaire. Data analyzed using SPSS v23.0; the initial analysis included descriptive statistics. Continuous and ordinal variables were compared using t-test or Mann-Whitney U test, and ANOVA or Kruskal-Wallis test, as appropriate; Chi-square test was used for categorical variables. Spearman correlation coefficient was calculated to determine the correlation between IGD score and depression and anxiety scores. RESULTS: A total of 726 high school gamers were involved, 87% of whom were Saudi, with a mean age of 16.92 years and 45% were from public schools. The mean IGD score was 18.12, and the prevalence of IGD was 21.85%. Students who spent ≥4 h/day on weekdays or ≥6 h/day at weekends on videogames and gamers who spent ≥200 Saudi Riyals per month on gaming had significantly higher mean IGD scores (P < 0.001). Gamers who used PC/laptop for gaming had significantly higher IGD scores compared to those who used other devices (P = 0.002). Action, fight, open-world games, and games with violence were associated with significantly higher IGD scores. Among students with IGD, 21.7% had moderately severe/severe depression and 11.4% had severe anxiety. CONCLUSION: IGD is a concerning psychiatric disorder in male high school students. It is associated with certain gaming behavior and other mental problems. We recommend future larger-scale research that includes females as well.